2009
DOI: 10.1007/s11998-009-9171-7
|View full text |Cite
|
Sign up to set email alerts
|

High temperature friction and wear behavior of MoS2/Nb coating in ambient air

Abstract: MoS 2 coatings are well-known for their solid lubricant properties and used as self-lubricants in vacuum and inert gas environments, and such coatings are not used in atmospheric conditions because of their deteriorating tribology. The tribological performance of MoS 2 solid lubricant coatings in the different atmospheres has been improved by the codeposition of a small amount of another metal. In this study, the tribological behavior of MoS 2 /Nb coatings was investigated in ambient air at temperatures up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 18 publications
0
10
2
Order By: Relevance
“…This superb combination of concurrent ultralow friction coefficient and wear rate makes DPNC TiB 2 /MoS 1.7 B 0.3 an outstanding USL material. In Figure c, we show a wear rate versus friction-coefficient plot for the recently reported self-lubricating materials based on MoS 2 , including MoS 2 -metals (Au, Ti, Pb, Cr, Zr, W, Nb), MoS 2 -nonmetals (C, N, B, Si, GLC, a-C:H), and MoS 2 -others (PTFE, Pb/Ti, CrMoN, Ag/C, Sb 2 O 3 /Au); for comparison, MoS 2 , TiB 2 , TiN, and several other typical wear-resistant materials , are also included. All of the data shown here are obtained in the self-lubricating mode, i.e., without any external input, and measured in ambient air.…”
Section: Resultsmentioning
confidence: 99%
“…This superb combination of concurrent ultralow friction coefficient and wear rate makes DPNC TiB 2 /MoS 1.7 B 0.3 an outstanding USL material. In Figure c, we show a wear rate versus friction-coefficient plot for the recently reported self-lubricating materials based on MoS 2 , including MoS 2 -metals (Au, Ti, Pb, Cr, Zr, W, Nb), MoS 2 -nonmetals (C, N, B, Si, GLC, a-C:H), and MoS 2 -others (PTFE, Pb/Ti, CrMoN, Ag/C, Sb 2 O 3 /Au); for comparison, MoS 2 , TiB 2 , TiN, and several other typical wear-resistant materials , are also included. All of the data shown here are obtained in the self-lubricating mode, i.e., without any external input, and measured in ambient air.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15] The results showed that MoS 2 can work well at low temperatures, especially in vacuums, but it can be easily oxidized at high temperatures. The authors' previous experiments show that Mo will react with CaF 2 at high temperatures and forming CaMoO 4 on the worn surface.…”
Section: Introductionmentioning
confidence: 99%
“…Arslan et al. 22 examined the friction and wear performances of the MoS 2 –Nb coating on the AISI 52100 steel. Their results demonstrated that both the COF and wear rate are lowest at 100 ℃, and the coating is intensively oxidized at 300–500 ℃.…”
Section: Introductionmentioning
confidence: 99%
“…The nanoindentation test by Stoyanov et al 21 showed that the Au-MoS 2 coating possesses higher hardness, lower surface adhesion, and stronger wear resistance in comparison with the pure Au film. Arslan et al 22 examined the friction and wear performances of the MoS 2 -Nb coating on the AISI 52100 steel. Their results demonstrated that both the COF and wear rate are lowest at 100 C, and the coating is intensively oxidized at 300-500 C. Li et al 23 verified that the elastic modulus and hardness of the MoS 2 -Pb nanocomposite coating increase with the Pb content and the anti-oxidant property is the determinant of the coating's wear resistance in the humid environment.…”
Section: Introductionmentioning
confidence: 99%